Emotional maltreatment in family of origin and young adult romantic relationship satisfaction: A dyadic data analysis. (July 2018) - Peterson, Claire M.; Peugh, James; Loucks, Laura; Shaffer, Anne
The aims of the current study were to use dyadic data analysis to examine the associations of history of childhood emotional maltreatment to current relationship satisfaction among young adult romantic partners as moderated by the effects of hostile behavioral observations within these romantic couples. Our sample included 52 young adult romantic dyads recruited from a large southeastern university. Current relationship satisfaction and history of childhood emotional maltreatment were obtained via self-report; behavioral interactions were rated on a behavioral coding system to determine level of dyadic hostility. Results revealed a significant interaction effect: Females' history of childhood emotional maltreatment significantly predicted relationship satisfaction for women at low or average (but not high) levels of dyadic hostility. Our findings suggest that for young women, romantic relationship satisfaction is compromised by their own history of emotional maltreatment, particularly when the couple's conflict resolution style is characterized by low to average levels of hostility.